2020
DOI: 10.1099/mgen.0.000405
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-genome analyses reveal gene content differences between nontypeable Haemophilus influenzae isolates from chronic obstructive pulmonary disease compared to other clinical phenotypes

Abstract: Nontypeable Haemophilus influenzae (NTHi) colonizes human upper respiratory airways and plays a key role in the course and pathogenesis of acute exacerbations of chronic obstructive pulmonary disease (COPD). Currently, it is not possible to distinguish COPD isolates of NTHi from other clinical isolates of NTHi using conventional genotyping methods. Here, we analysed the core and accessory genome of 568 NTHi isolates, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…S4 and S5 online at doi.org/10.26188/14954931). This finding is consistent with prior studies of NTHi which reported finding no evidence for phylogenetic signals of geographical origin (53,54) or clinical source (54,55). However, whole-genome k-mer DAPC revealed distinct clustering of RCH CF isolates with others that were noninvasive, collected from the respiratory tract, isolated from children, and circulating in Australia (based on the respective individual discriminant functions, see Fig.…”
Section: Discussionsupporting
confidence: 91%
“…S4 and S5 online at doi.org/10.26188/14954931). This finding is consistent with prior studies of NTHi which reported finding no evidence for phylogenetic signals of geographical origin (53,54) or clinical source (54,55). However, whole-genome k-mer DAPC revealed distinct clustering of RCH CF isolates with others that were noninvasive, collected from the respiratory tract, isolated from children, and circulating in Australia (based on the respective individual discriminant functions, see Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Based on their clinical characteristics, it was difficult to differentiate NTHi isolates from among each clade since they were clinically diverse, which is consistent with other studies showing no correlation between the phylogenetic classification and clinical or geographical origins [ 12, 45 ]. However, Kc et al [ 46 ] classified NTHi isolates into eight clades in which, despite having COPD strains distributed among all the clades, they could differentiate between COPD and non-COPD strains according to the composition of the accessory genome. This suggests that further studies are needed to improve the classification of NTHi strains and to find an association between the clades, the composition of the accessory genome, clinical data and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Hia and HMW adhesins, Hif pilus, and IgA-proteases are Hi virulence factors that are also differentially present in strains (56,57) and play a role in colonisation of specific niches like the respiratory tract (5861). Genome-wide association analysis could potentially identify other contributing factors (62), however this is beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%